Educational Integration in the Regional University Cluster - A. V. Kiryakova; S. M. Kargapoltsev; N. A. Kargapoltseva (Высшее образование в России, 2018)
In the context of continuing educational modernization, the paper identifies the areas of productive interaction between subjects of general, complementary and professional education in the expanding space of university cluster. The authors show the system-forming role of a modern university in the formation and development of the information environment of educational integration. The paper also presents a long-term experience of the Association “Orenburg University (Academic) District”, which is an assignee of the Orenburg Educational District, – on the development and implementation of innovative forms and methods of regional educational cooperation, the realization of the educational potential of networking in the pedagogical support of gifted children, the information development of students’ personality, the promotion of teachers’ professional development, the formation of schoolchildren’s and students’ research culture.